The presubiculum links incipient amyloid and tau pathology to memory function in older persons. (5th May 2020) - Jacobs, Heidi I.L.; Augustinack, Jean C.; Schultz, Aaron P.; Hanseeuw, Bernard J.; Locascio, Joseph; Amariglio, Rebecca E.; Papp, Kathryn V.; Rentz, Dorene M.; Sperling, Reisa A.; Johnson, Keith A.
Abstract : Objective: To identify the hippocampal subregions linking initial amyloid and tau pathology to memory performance in clinically normal older individuals, reflecting preclinical Alzheimer disease (AD). Methods: A total of 127 individuals from the Harvard Aging Brain Study (mean age 76.22 ± 6.42 years, 68 women [53.5%]) with a Clinical Dementia Rating score of 0, a flortaucipir tau-PET scan, a Pittsburgh compound B amyloid-PET scan, a structural MRI scan, and cognitive testing were included. From these images, we calculated neocortical, hippocampal, and entorhinal amyloid pathology; entorhinal and hippocampal tau pathology; and the volumes of 6 hippocampal subregions and total hippocampal volume. Memory was assessed with the selective reminding test. Mediation and moderation analyses modeled associations between regional markers and memory. Analyses included covariates for age, sex, and education. Results: Neocortical amyloid, entorhinal tau, and presubiculum volume univariately associated with memory performance. The relationship between neocortical amyloid and memory was mediated by entorhinal tau and presubiculum volume, which was modified by hippocampal amyloid burden. With other biomarkers held constant, presubiculum volume was the only marker predicting memory performance in the total sample and in individuals with elevated hippocampal amyloid burden. Conclusions: The presubiculum captures unique AD-related biological variation that is not reflected in total hippocampal volume. Presubiculum volume may be a promising marker of imminent memory problems and can contribute to understanding the interaction between incipient AD-related pathologies and memory performance. The modulation by hippocampal amyloid suggests that amyloid is a necessary, but not sufficient, process to drive neurodegeneration in memory-related regions.